Endothelial Zmiz1 modulates developmental angiogenesis in the retina - Patel, Nehal R.; Bavishi, Shreya A.; Bartoletti, Adella P.; K C, Rajan; Blanks, Avery; Carter, Kelsey; Chiang, Mark Y.; Meadows, Stryder M. (Frontiers in Cell and Developmental Biology, 2025)
Angiogenesis is a highly coordinated process involving the control of various endothelial cell behaviors. Mechanisms for transcription factor involvement in the regulation of endothelial cell dynamics and angiogenesis have become better understood, however much remains unknown, especially the role of non-DNA binding transcriptional cofactors. Here, we show that Zmiz1, a transcription cofactor, is enriched in the endothelium and critical for embryonic vascular development, postnatal retinal angiogenesis, and pathological angiogenesis in a model of oxygen-induced retinopathy (OIR). In mice, endothelial cell-specific deletion of Zmiz1 during embryogenesis led to lethality due to abnormal angiogenesis and vascular defects. Inducible endothelial cell-specific ablation of Zmiz1 postnatally resulted in impaired retinal vascular outgrowth, decreased vascular density, and increased vessel regression. In addition, angiogenic sprouting in the superficial and deep layers of the retina was markedly reduced. Correspondingly, vascular sprouting in fibrin bead assays was significantly reduced in the absence of Zmiz1, while further in vitro and in vivo evidence also suggested deficits in EC migration. In agreement with the defective sprouting angiogenesis phenotype, gene expression analysis of isolated retinal endothelial cells revealed downregulation of tip-cell enriched genes upon inactivation of Zmiz1. Lastly, our study suggested that endothelial Zmiz1 is critical for intraretinal revascularization following hypoxia exposure in the OIR model. Taken together, these findings begin to define the previously unspecified role of endothelial Zmiz1 in physiological and pathological angiogenesis.